PENGARUH Repellent BUAH MENGKUDU (Morinda Citrifolia L.) TERHADAP DAYA PROTEKSI HISPAN NYAMUK Aedes Aegypti SEBAGAI SUMBER BELAJAR BIOLOGI SMA - Putri Pawitri; Achyani Achyani; Suharno Zen (EDUBIOLOCK, 2020)
Noni fruit (Morinda citrifolia L.) is one of Indonesian’s original plants thathave potential as repellent or insect repellent. Noni fruit (Morinda citrifoliaL.) contains several compounds such as saponin, and flavonoids. Thesecompounds has an effect as toxic to insects and even causing death for insects.Saponins can enter through the mosquito’s respiratory organs of Aedesaegypti mosquitoes and could affect their protection. The purpose of thisresearch is to know whether there is influence of Noni fruit (Morinda citrifoliaL.) on the adultAedes aegypti mosquito suction protection, and to know theapplication of the research result in the form of practicum worksheet oninsekta material. The research design used was Completely RandomizedDesign (RAL), where the experiment conductedin four kinds of concentration0% (as control -), 6%, 8%, 10% and factory product positive control(+) at 3times repetition. The parameters observed were the protection power of Aedesaegypti mosquitoes. The result of the research showed that2tabel249,970,10hitungxx on α 0,05 so it can be concluded that there is significant influence on the concentration variation of Noni fruit (Morindacitriolia L.) extract to the Aedes aegypti mosquitoes protection. The mosteffective concentration is shown at a concentration of 10% where there is only1 Aedes aegypti mosquitoes perched.The validation result of learningresources indicates that the learning resources in the form of PracticumWorksheet are appropriate to use as a source of learningbiology in Insektamaterial.